Castor Seed from Melkasa Agricultural Research Centre, East Showa, Ethiopia and it’s biodiesel performance in Four Stroke Diesel Engine - Tesfahun Tegegne Akanawa; Haimanot Gebrehiwot Moges; Ramesh Babu; Daniel Bisrat (Center of Biomass & Renewable Energy (CBIORE), 2014)
This study focused in investigating the fuel properties of Castor oil Methyl Ester (CME) and its blend with diesel fuel in running a diesel engine. Engine tests have been carried out with the aim of obtaining comparative measures of torque, power, and specific fuel consumption. Castor oil was extracted by using a mechanical pressing machine and trans-esterification was made by methyl alcohol and potassium hydroxide as a catalyst. So that its viscosity and density were reduced and by increasing its volatility. By following the procedures given in American Society for Testing and Materials (ASTM) book the fuel characteristics were identified whether it fulfil the requirements needed to be used as a fuel in internal combustion engines or not. From the characterization result, it was proved that trans-esterified castor oil was found to be a promising alternative fuel for compression ignition (diesel) engines. But the viscosity of CME was still higher and the energy content was a little bit less as compared to petro diesel. To solve these problems CME was blended with petro diesel in some proportion (B5, B10, B20, B40, B80). The torque, power and brake specific fuel consumption performances of CME and its blends with petro diesel were tested in a four stroke diesel engine. The analyzed results were compared with that of petro diesel and found to be very nearly similar, making CME a suiTable alternative fuel for petro diesel.